2014
DOI: 10.1021/ma5007039
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Photo-Induced Sequential CuAAC and Thiol–Ene Click Strategy for Bioactive Macromolecular Synthesis

Abstract: Conceptually new one-pot photoinduced sequential click reactions were implemented to yield novel block copolymers with the ability for cell adhesion. Poly(ε-caprolcatone) possessing clickable functional groups at the chain ends, namely α-alkynyl-ω-alkenyl-poly(ε-caprolactone) (A-PCL-MA), was prepared by ring-opening polymerization of ε-caprolactone using propargyl alcohol in the presence of stannous octoate at 110 °C followed by esterification with methacrylic acid. Azide-functional poly(methyl methacrylate) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…1 The advantages of photoinitiating this reaction complement its already significant value within synthetic methodologies, bioconjugation, labeling, surface functionalization, dendrimer synthesis, polymer synthesis, and polymer modification 2-7 by adding spatial and temporal control. 8,9 Scheme 1 illustrates the traditional CuAAC reaction, where the key component allowing this reaction to occur on a reasonable time scale is the copper(I) catalyst. In the absence of Cu(I), the reaction proceeds as much as 7 orders of magnitude more slowly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The advantages of photoinitiating this reaction complement its already significant value within synthetic methodologies, bioconjugation, labeling, surface functionalization, dendrimer synthesis, polymer synthesis, and polymer modification 2-7 by adding spatial and temporal control. 8,9 Scheme 1 illustrates the traditional CuAAC reaction, where the key component allowing this reaction to occur on a reasonable time scale is the copper(I) catalyst. In the absence of Cu(I), the reaction proceeds as much as 7 orders of magnitude more slowly.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,12-19 In particular, with the use of a photoinitiator, the reduction of copper can be triggered upon exposure to either UV or visible light (Figure 1A), depending on the specific photoinitiator used and its absorption spectra. 1,20 Adzima et al showed that the photo-CuAAC reaction can be applied in an aqueous environment to perform photolithography and postpolymerization modification of hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[23,[31][32][33] In the related work from the authors' laboratory, linear and hyper-branched polymers and block polymers with thermoactive-, photo-, electro-, and bio-functionalities were successfully prepared through CuAAC reactions. [34][35][36][37][38][39] These reactions can also be triggered by electrochemical and photochemical activation. [38,40] Moreover, due to their ability to be orthogonal, they can be combined with other polymerization and coupling processes in a sequential and simultaneous manner.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, photogenerated free radicals stemming from various photoinitiators or photoinduced electron transfer reactions have been reported as efficient protocols to reduce Cu II , giving rise to successful CuAAC transformations. [16][17][18][19][20][21] The use of photoinitiators or photosensitizers brings the advantage of extending the spectral sensitivity to higher wavelengths in accordance with the optical behavior of the initiator, thus giving reactions which proceed with low energetic requirements and mild conditions. Photoinduced CuAAC also offers the opportunity of providing spatiotemporal control over the reaction which is rarely the case with its thermal counterparts.…”
Section: Abstract: Copper(ii) Thioxanthone Carboxylate Photoinduced Cmentioning
confidence: 99%